Gold mining, indigenous land claims and conflict in Guyana's hinterland. (February 2017) - Hilson, Gavin; Laing, Timothy
Abstract: In recent decades, Guyana's gold-rich interior has been the location of numerous, mostly low-latent, conflicts. In each case, groups of Afro and Indo-Guyanese originating from the country's coastal cities and towns – popularly referred to as 'Coast Landers' – have clashed with indigenous Amerindians over control of remote parcels of land containing gold deposits. Each appears to have a valid argument in support of its position: the former contend that they are legally entitled to work these lands, having obtained the requisite permits from the central government to mine for gold, whilst the latter maintain that such decisions constitute a breach of their human rights, and draw attention to key legislation in support of their case. This article broadens understanding of the dynamics of these conflicts by reflecting more critically on the arguments presented by both parties. Drawing heavily on research conducted in Mahdia-Campbelltown, one location where frictions between Coast Lander mining groups and Amerindians are particularly serious, it is argued that these disputes are not about control of gold riches as is popularly believed but rather a product of deeply-rooted ethnic tensions between these parties. Highlights: Guyana's gold-rich interior is the location of numerous, mostly low-latent, conflicts. These conflicts involve 'Coast Lander' Afro and Indo-Guyanese groups with mining interests and indigenous Amerindians. There is a misconception that these conflicts stem from Amerindians' desires to secure gold-rich mining territories. These conflicts are complex, with underlying ethnic differences between the two groups being the chief cause. A case study of Mahdia-Campbelltown, one of Guyana's main gold-mining communities, is used to illustrate these points.